Exploring the Impacts of Peer Interaction in ESL University Students’ Argumentative Writing Activities via WhatsApp (International Journal of Language, Literacy and Translation, 2025)
This study explores whether peer interaction in WhatsApp discussion affect participants' writing achievement. The initial phase of this study is to improve the participants’ ability to share ideas and discussions on the eight argumentative topics in the WhatsApp group through peer interaction. Eight undergraduate students from University Sains Malaysia were chosen purposely based on their low proficiency in MUET results of Band 2. In this qualitative study, twenty open-ended interview questions were added to understand the participants’ views and experiences on peer interaction in WhatsApp. The open-ended interview questions were validated by three language experts from three local universities in Malaysia. The participants’ writing scores were also recorded to measure their writing achievement in order to answer the research questions. The writing achievement was on the argumentative writing essays that the participants sent every week for eight weeks after three days of peer interaction in WhatsApp. The study showed significant improvement that the participants’ perceived a strong peer interaction in their discussion via WhatsApp. The participants were able to interact with their peers and used the ideas shared in supporting their arguments in the essay writing. Relatedly, these promising improvements in the students’ participation and the findings found that the participants’ peer interaction had created a positive community environment and increased their writing achievement.